Additional new species of Grouvellinus Champion 1923 (Insecta, Coleoptera, Elmidae) discovered by citizen scientists and DNA barcoded in the field applying a novel MinION-based workflow. Issue 41 (10th November 2019) - Freitag, Hendrik; Molls, Christian; Bouma, Aglaia M.; Garces, Jhoana M.; Rossato, Marzia; Cosentino, Emanuela; Delledonne, Massimo
ABSTRACT: Four new species, Grouvellinus nigerquadratus sp. nov., G. cruxniger sp. nov., G. luciaensis sp. nov., and G. borneensis sp. nov., are described from Borneo and illustrated in detail. Two additional species of the genus which remain undescribed are briefly diagnosed. The material was collected during Taxon Expeditions' field course which involved citizen scientists, students and taxonomists. Specimens were collected at altitudes between 270 m and 750 m above sea level using fine-meshed hand-nets and blacklight traps. The morphological species delimitation based on morphology was supplemented and congruent with mtDNA sequences which are the first DNA barcodes for the genus from Borneo. They were obtained in the field using a newly developed rapid and accurate MinION-based workflow. The inter – and intraspecific genetic distances and the problems regarding cryptic species delimitation are discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:4B1D0F3D-B303-46A5-86B4-C23454192327